THE PSYCHOLOGICAL DEPTHS OF GRAHAM GREENE’S CHARACTERS - Tulaboeva , Madina (Educational Research in Universal Sciences, 2023)
In this article, we will explore Greene’s portrayals of psychological depth in his characters. We will discuss the ways in which he explores the inner lives of his characters, analyzing the techniques he uses to reveal their deepest motivations and fears. We will also examine the complexity of his characters and the ways in which he portrays the human condition through their struggles. Finally, we will discuss the significance of Greene’s characterization in the literary world and the influence it has had on other writers.